Mechanism and Control Technology of Rockburst Induced by Thick Hard Roof and Residual Coal Pillar: A Case Study - Wenjie Liu; Ke Yang; Xiang He; Zhainan Zhang; Rijie Xu (Geofluids)
Rockburst caused by the fracture of thick hard roof and the instantaneous instability of residual coal pillar seriously jeopardize the deep coal mining safety. This study takes Boertai Coal Mine, Shendong, China, as the engineering background, in which dynamic instability mechanisms of the gob-side roadway surrounding rock are analyzed by integrating field research, theoretical analysis, and numerical simulation. The results show that the overlying residual coal pillar, side abutment pressures, and front abutment pressures together induce high static stresses in the surrounding rock of the gob side roadway, with peak values exceeding the in situ stress by one order of magnitude. High stresses accumulated in the goaf-side roadway surrounding rock can easily induce dynamic disaster. With the working face advanced, overburdens are caved in succession, resulting in a continuously decreasing of the overlying residual coal pillar width, once the working face entered the influence area of the residual coal pillar. As the morphology of abutment pressure in the residual coal pillar changes from “unimodal distribution” to “bimodal distribution,” the residual coal pillar gradually changes from elastic state to plastic state. When the width of the overlying residual coal pillar is less than the critical width, the thick hard roof and residual coal pillar structure (THRRCPS) lose stability suddenly, resulting in strong dynamic load on the surrounding rock of gob-side roadway. In order to prevent the rockburst of the gob-side roadway under the influence of THRRCPS, regional and local prevention measures are adopted to mitigate the accumulation of stress in the thick hard roof and gob-side roadway surrounding rock by hydraulic fracturing technology and large diameter pressure relief drilling hole.